2016
DOI: 10.1111/jan.12959
|View full text |Cite
|
Sign up to set email alerts
|

Wearable monitors for patients following discharge from an intensive care unit: practical lessons learnt from an observational study

Abstract: Work is needed to understand wireless monitor comfort and design for acutely unwell patients. Product design needs to develop further, so patients are catered for in flexibility of monitor placement and improved comfort for long-term wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 21 publications
1
66
0
Order By: Relevance
“…Such risk models are invaluable tools for clinical decision making and, in the context of ICU discharge, can provide information with which to plan complex de-escalations of care. For example, patients deemed to be at high-risk of readmission may benefit from continued close monitoring,16 since early detection of deterioration is a strong predictor of outcome 17 18…”
Section: Introductionmentioning
confidence: 99%
“…Such risk models are invaluable tools for clinical decision making and, in the context of ICU discharge, can provide information with which to plan complex de-escalations of care. For example, patients deemed to be at high-risk of readmission may benefit from continued close monitoring,16 since early detection of deterioration is a strong predictor of outcome 17 18…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, software companies or engineers usually develop technologies using a “top‐down” approach, assuming their IHT solutions will be welcomed and used by patients. Yet, without formally checking technology acceptance, or patients’ openness or willingness to use these technologies in advance, it is not surprising that patients often refuse to use or abandon such technologies prematurely, with rates of patient dropout in technology‐related studies of up to 67.7% (Jeffs et al., ). This occurs for a variety of reasons: patients do not feel a need for the technology, perceive it as too intrusive, demanding, or difficult, have technical problems or problems with the graphical user interfaces, or have insufficient skills to use the technology (Cruz‐Correia et al., ; Or & Karsh, ; Stoop, van't Riet, & Berg, ; Williams, Nicholas, & Huntington, ).…”
mentioning
confidence: 99%
“…Our results therefore represent minimum durations. Other studies with continuous monitoring of vital signs in general wards have also reported issues with data incompleteness with comparable amount of missing data [24][25][26].…”
Section: Discussionmentioning
confidence: 99%